The Effects of Climatic Variability on the Feeding Ecology of the Scalloped Hammerhead Shark (Sphyrna lewini) in the Tropical Eastern Pacific - Arnés-Urgellés, Camila; Salinas-de-León, Pelayo; Rastoin-Laplane, Etienne; Vaca-Pita, Leandro; Suárez-Moncada, Jenifer; Páez-Rosas, Diego (Frontiers in Marine Science, 2021)
Climatic variability changes ocean productivity and generates systematic cascading effects in marine food webs. Studying the feeding ecology of top predators, such as sharks, can provide insights into the overall health of marine ecosystems. We conducted a 4-year study to evaluate seasonal and inter-annual trophic variations and their relationship with El Niño Southern Oscillation (ENSO) on the largest aggregation of scalloped hammerhead shark (Sphyrna lewini) in the Tropical Eastern Pacific (TEP). We used δ13C and δ15N signatures to gain a better understanding of hammerheads’ feeding strategies as well as variations of their isotopic niche. Our results suggest that the hammerhead sharks in the Galapagos Marine Reserve respond to climatic fluctuations, with La Niña event potentially benefiting their trophic needs as the overall marine productivity increased in the region. This work is the first of its kind in the TEP and provides insights on how climate variability influences the feeding ecology of this critically endangered species. It also highlights the need to incorporate climate-related conservation strategies into the management of this species since ENSO events become more frequent and intense in the face of climate change.